Library and Information Science in Developing Countries : contemporary issues - Tella, Adeyinka, 1972-; Issa, Abdulwahaab Olanrewaju, 1967- (Hershey, PA : Information Science Reference, 2012)
"This book explores the relationship between global technology development and the impact of new technologies on library practice, library education, and information science"--Provided by publisher.
Fostering and developing leadership amongst library staff at the University of Zambia Library / Christine Wamunyima Kanyengo -- Pakistan Library and Information Council : a proposal / Midrar Ullah, Khalid Mahmood -- Modernisation of a traditional library / Mehtab Alam Ansari -- Marketing library and information services for effective utilization of available resources : the 21st century librarians and information professionals : which ways and what works? / Tella, Adeyinka ; Ojo, Rachael -- Strategies for marketing an academic library in an African setting / Sylvia A. Ogola, Japhet Otike -- The significance of marketing in library and information science / Monday Obaidjevwe Ogbomo -- Marketing libraries : adopting marketing strategies in Nigerian libraries / Olamidipupo Solomon -- Libraries and preservation of indigenous knowledge in developing countries : the Nigeria experience / Omopupa, K.T. ; Bashorun, M.T. ; Isah, A -- The school librarian in rural China : a stranger among her people / Peter Warning, James Henri -- The future of readership development : how ICTs have influenced user habits and library acquisitions / Elisam Magara -- Status of information ethics teaching at the School of Information Sciences, Moi University, Kenya / Henry N. Kemoni -- An assessment of the perception of library school students towards librarianship at the University of Ilorin : a pilot study / Abdulwahaab Olanrewaju Issa -- Demystifying digital scholarship / Stephen Mutula -- Establishing the digital library : don't ignore the library standards and don' forget the training needed / Alan Hopkinson -- A review of e-government services in Nigeria / Gbola Olasina -- Digital libraries : their challenges and issues in the perspectives of developing countries like India / N.Swaminathan -- Information flow and democratic governance : an analysis of the African experience / F.A. Aremu, H.T. Saka -- Librarians, records managers, and e-government / Cathrine T. Nengomasha -- Information services provision to person with visual impairment in Nigeria : the salient issues / Niran Adetoro -- Organisation of information and the information retrieval system / Edeama O. Onwuchekwa -- Social media in library and information centers / Ayodele John Alonge -- Bibliometric analysis of DECIDOC journal of library & information technology / S. Thanuskodi -- Cataloguing and classification of library resources in the 21st century / Lydia O. Adedibu, Evelyn O. Akinboro, and Titilola A. Abdul salam.
"Premier reference source"--Cover.
Includes bibliographical references and index (p. 361-364).
Keywords: Library science -- Developing countries; Information science -- Developing countries; Libraries -- Developing countries; Library education -- Developing countries